KEBIJAKAN PENDIDIKAN DI INDONESIA PADA MASA PANDEMI COVID-19 BESERTA DAMPAKNYA - Nur Alif Masitoh; Heri Kurnia (Academy of Education Journal, 2022)
The learning process must continue to be carried out even in the covid-19 pandemic situation. The covid-19 pandemic has changed the order of the educational process, which was originally face-to-face at school, to face-to-face virtual. The online learning process requires educators to create appropriate and fun learning models and methods, so that learning materials can reach students and can be understood by students. This article aims to describe education policies in Indonesia during the covid-19 pandemic and their impacts. The data in this article were obtained through literature studies or library research and case studies by collecting information from various sources. The results showed that education policies during the covid-19 pandemic were implemented using online learning methods and offline learning which were carried out with strict health protocols and there was a division of time for students to come to school. However, the impact of online learning greatly affects students and parents both in terms of economics and psychology.